FUNGSI SOSIAL PANTANG LARANG MASYARAKAT KUANSING - Rismai Astuti; Elmustian Rahman; Abdul Jalil (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThis study is a step in understanding the social function of abstinence forbids Kuansing society. Social function of abstinence forbids the two words are quite difficult to distinguish. Because both have almost the same objective determination about something God-given. Social function of abstinence forbids in search based on observations, interviews, and recording. Accordingly, the approach used in analyzing the social function of abstinence forbids dialogisme and this research is categorized as qualitative research. The method used is descriptive method. The data were found to be described by the theory of social functions abstinence ban, after which a dialogue with dialogisme analysis. The results of abstinence forbids social function based on the analysis of social function dialogisme is very closely related to the use of social functions themselves in order to be understood by many, while abstinence is associated with God forbids because it is God power to determine the terms something every human being and other creatures-her. .Keywords: social function of abstinence forbids